2017
DOI: 10.1177/1745691617718358
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Challenges in Scientific Research on Mindfulness and Meditation

Abstract: Van Dam et al. raise a number of critical issues in contemporary research on mindfulness and meditation and offer a prescriptive agenda for future work in this area. While we agree with all of the key points made in their article, there are a number of important issues omitted that are central to a comprehensive agenda for future research in this area. This commentary highlights five key points: (a) Many of the key methodological issues the article raises are not specific to research on mindfulness; (b) contem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 12 publications
0
46
0
2
Order By: Relevance
“…Lastly, while the 39-item FFMQ used in this study has demonstrated very satisfactory test-retest reliability and construct validity (59), there is a debate in literature about the insufficient construct validity in self-reporting measures of mindfulness (55). Indeed, there is a widespread acknowledgment that information based on self-reported measures of complex psychological characteristics, such as mindfulness, cognitions and emotions, are inadequate (60). The use of a multimodal approach, where neurobiological and behavioral assessments can be used to capture attentional capacity, may be helpful to mutually inform mindfulness and establish process models of mindfulness for future research (55).…”
Section: Study Strengths Limitations and Recommendations For Futurementioning
confidence: 78%
“…Lastly, while the 39-item FFMQ used in this study has demonstrated very satisfactory test-retest reliability and construct validity (59), there is a debate in literature about the insufficient construct validity in self-reporting measures of mindfulness (55). Indeed, there is a widespread acknowledgment that information based on self-reported measures of complex psychological characteristics, such as mindfulness, cognitions and emotions, are inadequate (60). The use of a multimodal approach, where neurobiological and behavioral assessments can be used to capture attentional capacity, may be helpful to mutually inform mindfulness and establish process models of mindfulness for future research (55).…”
Section: Study Strengths Limitations and Recommendations For Futurementioning
confidence: 78%
“…Even though attention and executive control processes could be influenced by yoga and other mindfulness practices (Jha et al, 2007;Teper and Inzlicht, 2013), the mechanism through which such practices enhance attention and executive control remains unknown. Scholars have pointed out several limitations of studies examining the cognitive enhancement of yoga and mindfulness practices, namely, a lack of specificity in defining the construct underlying the practice, lack of precision with measuring the construct, and failure to establish a link between the construct and the cognitive function presumably enhanced (Davidson and Dahl, 2018;Van Dam et al, 2018). The practice of yoga comprises postures (asanas) and breathing (pranayama) (Woodyard, 2011;Sengupta, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has never been easier and less costly to obtain large samples on MBPs, which should then facilitate devising many kinds of novel study designs and foci. Large sample size data sets make it possible, e.g., to study individual differences of MBP participants in a way face-to-face MBP studies lack the power to do (Davidson and Dahl 2018). Online MBPs are highly scalable and, if beneficial, as early evidence indicates (Spijkerman et al 2016), can expand MBP reach and resulting benefits to new populations.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…An accumulating evidence base now points to mindfulness meditation having beneficial effects on, at least, anxiety and depression (Creswell 2017;Goyal et al 2014;de Vibe et al 2017). On the other hand, the research community has seen recent voicing of concern over "mindfulness hype" getting ahead of the science (Van Dam et al 2018;Davidson and Dahl 2018). Though the field sees hundreds of new studies each year, it is still lacking in large sample studies that shed light on more nuanced mechanisms of mindfulness meditation and its impact on well-being or adversity.…”
mentioning
confidence: 99%